Photovoltaic activity of WSe2/Si hetero junction. (December 2019) - Pataniya, Pratik M.; Zankat, Chetan K.; Tannarana, Mohit; Patel, Abhishek; Narayan, Som; Solanki, G.K.; Patel, K.D.; Jha, Prafulla K.; Pathak, V.M.
Graphical abstract: Highlights: We demonstrate fabrication of fast switchable WSe2 /Si p-n heterojunction. Device showed highest Jsc of 1.54 mA/cm 2 and Voc of 0.34 V at 18 mW/cm 2 power intensity. Heterojunction exhibited broad spectral photoresponse in range from 390 to 1088 nm. The device showed excellent response in temperature range 200 to 300 K. Abstract: Propelled by the development of layered transition metal dichalcogenides, heterojunctions have captivated tremendous attention due to various excitonic mechanisms assisted strong light-matter interaction. We demonstrate liquid phase exfoliation of WSe2 and fabrication of fast switchable WSe2 /Si heterojunction. The heterojunction device showed obvious rectifying nature with ideality factor of 1.21 and it is explored under white illumination at power intensities varying from 5 to 18 mW/cm 2 . The WSe2 /Si heterojunction photovoltaic device exhibited excellent transient photoresponse with highest responsivity of 86.11 mA/W and 23 ms response time under white light. Besides, heterojunction exhibited excellent photoresponse in broad spectral range from 390 to 1088 nm with highest photoresponsivity of 122.2 mA/W for 780 nm illumination. The device showed excellent response in temperature range 200 to 300 K. Eventually, the results advocate the huge significance of WSe2 /Si heterojunction for photovoltaic cell and photodetection.